Maternal immunization increases nestling energy expenditure, immune function, and fledging success in a passerine bird - Burness, Gary (Biol Open, 2018)
Female birds transfer maternally derived antibodies (matAb) to their nestlings, via the egg yolk. These antibodies are thought to provide passive protection, and allow nestlings to avoid the costs associated with mounting an innate immune response. To test whether there is an energetic benefit to nestlings from receiving matAb, we challenged adult female tree swallows (Tachycineta bicolor) prior to clutch initiation with either lipopolysaccharide (LPS) or saline (Control). Following hatching, one half of each female's nestlings were immunized on day 8 post-hatch with LPS or saline, and the 4-h post-immunization nestling metabolic rate (MR) was measured. There was no difference in either LPS-reactive antibodies or total Ig levels between offspring of immunized and non-immunized mothers on day 6 or 14 post-hatch, possibly reflecting a relatively short half-life of matAbs in altricial birds. Additionally, we found no evidence that nestlings from LPS-immunized mothers could avoid the growth suppression that may result from activation of an inflammatory response. Unexpectedly, we found that control nestlings from LPS mothers had higher resting MR than control nestlings of control mothers. We attribute the increased MR to the costs associated with a general non-specific enhancement of immune function in nestlings from LPS-immunized mothers. Consistent with enhanced immune function, nestlings of immunized mothers had a more robust inflammatory response to phytohaemagglutinin and higher fledging success. Our results suggest that maternal antigen exposure pre-laying can result in increased fitness for both mothers and offspring, depending on food availability.